2005
DOI: 10.1128/aac.49.1.289-301.2005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Multidrug Efflux Operon acrEF by Insertional Activation with IS 1 or IS 10 Elements in Salmonella enterica Serovar Typhimurium DT204 acrB Mutants Selected with Fluoroquinolones

Abstract: High-level fluoroquinolone (FQ) resistance in Salmonella enterica serovar Typhimurium phage type DT204 has been previously shown to be essentially due to both multiple target gene mutations and active efflux by the AcrAB-TolC efflux system. In this study we show that in intermediatly resistant acrB-inactivated serovar Typhimurium DT204 mutants, high-level resistance to FQs can be restored on in vitro selection with FQs. In each FQ-resistant mutant selected from serovar Typhimurium DT204 acrB mutant strains, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 51 publications
3
71
0
Order By: Relevance
“…Notably, this mutation was present in clinical isolates from cystic fibrosis (CF) patients. Another interesting phenomenon was observed for Salmonella enterica serovar Typhimurium, in which the presence of the IS1 or IS10 insertion element in the promoter region upstream of the genes encoding the AcrEF pump enhanced the transcription of this operon, thereby conferring resistance to fluoroquinolones (191). Nonetheless, the vast majority of mutations affecting antibiotic export by efflux systems occur in genes encoding proteins with a regulatory function.…”
Section: Mutational Resistance Related To Efflux Pumpsmentioning
confidence: 99%
“…Notably, this mutation was present in clinical isolates from cystic fibrosis (CF) patients. Another interesting phenomenon was observed for Salmonella enterica serovar Typhimurium, in which the presence of the IS1 or IS10 insertion element in the promoter region upstream of the genes encoding the AcrEF pump enhanced the transcription of this operon, thereby conferring resistance to fluoroquinolones (191). Nonetheless, the vast majority of mutations affecting antibiotic export by efflux systems occur in genes encoding proteins with a regulatory function.…”
Section: Mutational Resistance Related To Efflux Pumpsmentioning
confidence: 99%
“…Eaves et al (14) reported that acrB, acrF, and acrD are coordinately regulated and that their expression influences the expression of the transcriptional activators marA and soxS. Furthermore, it has been reported that integration of an IS1 or an IS10 element in the upstream region of the acrEF operon causes increased expres-sion of acrEF (52). These examples illustrate the complexity and diversity of the mechanisms regulating bacterial multidrug efflux pumps.…”
mentioning
confidence: 97%
“…A spontaneous laboratory mutant of E. coli has also been selected with IS186 in acrR or IS2 upstream of acrEF (67). An IS element inserted in mexR has also been described for a clinical isolate of P. aeruginosa and for acrS (the putative repressor of acrEF) of S. enterica serovar Typhimurium DT204 (20,150). In the latter case, the mutant was selected in vitro on high concentrations of fluoroquinolone from a veterinary isolate.…”
Section: Insertion Sequencesmentioning
confidence: 99%